Kewarisan Beda Agama di Nagari Persiapan Bancah Kariang Kecamatan Kinali Kabupaten Pasaman Barat - Elfia, E.; Surwati, Surwati; Fajri, Yan (Institut Agama Islam Negeri Curup, 2021)
This study aims to find out the basis and reasons for heirs of different religions to get inheritance from heirs who died and how the distribution of inheritance is carried out by the community in Nagari Bancah Kariang, Kinali District, West Pasaman Regency. This research is an empirical research using a socio-legal approach. The data used is qualitative data which is analyzed descriptively qualitatively. The findings from this study are the basis and method of dividing inheritance of different religions in Nagari Preparation Bancah Kariang, Kinali District, West Pasaman Regency is based on the habits that have been carried out by the family so that it has been passed down from generation to generation until now and the distribution of inheritance is carried out equally, regardless of religion. in a family member after the death of an heir. This is done with the aim of maintaining harmony among his family and is considered a fair distribution of inheritance with a family system. Families that have family members of different religions also get an equal share and do not differentiate the income from inheritance to their children to strengthen the relationship between children and their parents. The practice carried out by the Nagari Bancah Kariang community clashes with the Prophet's hadith which clearly states that different religions are a barrier to inheriting under any pretext because ikhtilaf al-diin is one of the mawani '(barriers) in Islamic inheritance law.